"What should I do when I get home?" treatment plan discussion at discharge between specialist physicians and older in-patients: mixed method study - Tahreem Ghazal Siddiqui; Socheat Cheng; Marte Mellingsæter; Ramune Grambaite; Pål Gulbrandsen; Christofer Lundqvist; Jennifer Gerwing (BMC, 2020)
Abstract Background During discharge from hospital, older patients and physicians discuss the plan for managing patients' health at home. If not followed at home, it can result in poor medication management, readmissions, or other adverse events. Comorbidities, polypharmacy and cognitive impairment may create challenges for older patients. We assessed discharge conversations between older in-patients and physicians for treatment plan activities and medication information, with emphasis on the role of cognitive function in the ongoing conversation. Methods We collected 11 videos of discharge consultations, medication lists, and self-reported demographic information from hospitalised patients ≥65 years at the Geriatric department in a general hospital. Mini Mental State Examination score < 25 was classified as low cognitive function. We used microanalysis of face-to-face dialogue to identify and characterise sequences of interaction focused on and distinguishing the treatment plan activities discussed. In addition to descriptive statistics, we used a paired-sample t-test and Mann-Whitney U test for non-parametric data. Results Patients' median age was 85 (range: 71-90);7 were females and 4 males. Median of 17 (range: 7 to 23) treatment plan activities were discussed. The proportions of the activities, grouped from a patient perspective, were: 0.40 my medications, 0.21 something the hospital will do for me, 0.18 someone I visit away from home, 0.12 daily routine and 0.09 someone coming to my home. Patients spoke less (mean 190.9 words, SD 133.9) during treatment plan activities compared to other topics (mean 759 words, SD 480.4), (p = .001). Patients used on average 9.2 (SD 3.1) medications; during the conversations, an average of 4.5 (SD 3.3) were discussed, and side effects discussed on average 1.2 (SD 2.1) times. During treatment plan discussions, patients with lower cognitive function were less responsive and spoke less (mean 116.5 words, SD 40.9), compared to patients with normal cognition (mean 233.4 words, SD 152.4), (p = .089). Conclusion Physicians and geriatric patients discuss many activities during discharge conversations, mostly focusing on medication use without stating side effects. Cognitive function might play a role in how older patients respond. These results may be useful for an intervention to improve communication between physicians and older hospitalised patients.